The Influence Of Compensation, Work Environment, And Organizational Commitment On Employee Performance (Case Study at PT Witan Prelsisi Indonesia) - Wachid Hasyim; Tri Wahju Wirjawan (Journal of Research in Social Science and Humanities, 2024)
Human resources are a very important element for companies so that a business runs well, good human resources are created by good management. Which is able to provide comfort for its employees. This study aims to examine the effect of compensation, work environment, and organizational commitment on employee performance. This type of research is quantitative research. This sampling uses a simple random technique which is a technique that is carried out randomly and comes from existing population members. The sample in this study were employees at PT Witan Presisi Indonesia, namely 90 people, and collecting data in this study included observation, distributing questionnaires, and literature study. Data analysis techniques in this study are validity test, reliability test, classical assumption test, multiple linear analysis and hypothesis testing. By using the SPSS Version 25 application program which shows the results that there is an influence and no effect on X on Y. Furthermore, it can be concluded partially that compensation has no effect and is not significant on employee performance seen from the results of tcount (1.212) ttable (1.987) and significance value (1.229) (0.05), the work environment has a positive and significant effect on employee performance seen from the results of tcount (4. 4117) ttable (0.05), 4117) ttable (1.987) and significance value (0.000) (0.05), and organizational commitment has a positive and significant effect on employee performance as seen from the results of tcount (3.371) ttable (1.987) and significance value (0.002) (0.05).